STUDI KELAYAKAN DESA BURAI SEBAGAI DESA WISATA DI KABUPATEN OGAN ILIR - Indah Kartika; Lisnini Lisnini; Esya Alhadi (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2020)
This research on Burai Village aims to determine and assess the feasibility of Burai Village as a tourist village in Ogan Ilir Regency. This type of research is descriptive qualitative using SWOT analysis. The result of the research is that Burai Village is feasible and can be used as a tourist village in Ogan Ilir Regency because it is supported by its geographical location, community culture, and existing village objects. The strategy used for the feasibility and development of Burai Village as a tourism village is the SO strategy by utilizing a large area of land for the construction of facilities and infrastructure to support tourism activities, making tour packages by using travel agents to sell tour packages to attract tourists to visit Burai Village, In collaboration with related agencies and public transport service providers to add routes to Burai Village and provide the maximum opportunity and role for the community in the development of tourist villages